2019
DOI: 10.1039/c8se00551f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size on the apparent electrocatalytic activity of LiMn2O4 for oxygen evolution

Abstract: Particle size influences the product current densities of LiMn2O4 where smaller particles showed higher faradic efficiency for the OER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 29 publications
(81 citation statements)
references
References 31 publications
9
69
1
2
Order By: Relevance
“…Our previous studies showed no evidence of morphological changes of the LiMn 2 O 4 nanoparticles in NaOH). [5,6] As the detected Mn loss during the first 5 cycles is similar for all LiOH electrolytes ( Figure S1) and also similar to the Mn loss reported in NaOH, [5] we expect that no changes in morphology occurred in the used LiOH electrolytes. In Figure 2a, the anodic and cathodic traces of the CV in NaOH were featureless except for the exponential rise due to oxygen evolution, [4][5] while there was a clear anodic shoulder and cathodic peak in the CV in LiOH.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Our previous studies showed no evidence of morphological changes of the LiMn 2 O 4 nanoparticles in NaOH). [5,6] As the detected Mn loss during the first 5 cycles is similar for all LiOH electrolytes ( Figure S1) and also similar to the Mn loss reported in NaOH, [5] we expect that no changes in morphology occurred in the used LiOH electrolytes. In Figure 2a, the anodic and cathodic traces of the CV in NaOH were featureless except for the exponential rise due to oxygen evolution, [4][5] while there was a clear anodic shoulder and cathodic peak in the CV in LiOH.…”
Section: Resultssupporting
confidence: 82%
“…We investigated the CV of 10 mM LiOH further as it showed a clear exponential rise in current density and emphasized the aforementioned differences to previous studies in NaOH and KOH (Figure c). The rising disk current density at high voltage was assigned based on the ring current (blue dashed line), which was set to reduce oxygen at 0.4 V vs. RHE and thus qualitatively detected the oxygen produced at the disk.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations